Nanostructured Al2O3-YAG-ZrO2 ternary eutectic components prepared by laser engineered net shaping. (15th May 2019) - Fan, Zhiqi; Zhao, Yitian; Tan, Qiyang; Mo, Ning; Zhang, Ming-Xing; Lu, Mingyuan; Huang, Han
Abstract: The present work proposed a novel 3D printing approach for fabricating ternary eutectic ceramics (Al2 O3 -YAG-ZrO2, or AYZ in short) using laser engineered net shaping (LENS) technique. Highly dense (≥98%) thin wall components with refined eutectic microstructures were successfully fabricated. The as-fabricated ceramic eutectics mainly consist of cellular eutectics with three phases interpenetrated. In each deposited layer, the solidified microstructure changes from planar to cellular along building direction. The evolution of characteristic dimension of microstructure can be well interpreted using Jackson-Hunt relationship. Irregular interpenetrating to regular fibrous eutectic structure transition occurs at boundary region of LENSed specimens, primarily due to much higher solidification rate. The texture of <0001>Al2O3 //<001>YAG //<001>ZrO2 is recognized at the interior region of LENSed eutectic part along building direction, but gradually tilts from central to edge due to change of cellular growth direction. The LENSed AYZ samples exhibit almost isotropic property, and have mechanical performances comparable to those fabricated using conventional direction solidification methods. Graphical abstract: Image 1